Interactive Effects of Situational Variables Regarding Teams’ Technical Performance in the UEFA Champions League - Yi, Qing; Yang, Jingyong; Wang, Xinlei; Gai, Yang; Gómez-Ruano, Miguel-Ángel (Frontiers in Psychology, 2022)
The aim of this study was to examine the interactive effects of situational variables (competition stage, match location, and match outcome) on teams’ technical performance in the UEFA Champion League. Match data of 19 technical actions and events were collected and classified into three groups (variables related to goal scoring, offense, and defense) during eight seasons (2009/2010 to 2016/2017). Repeated-measures analysis of variance (RMANOVA) was used to identify the differences in the technical performances among teams. Results showed that the significant differences in the technical performance between the group stage and the knockout stage were only found in dribble and yellow card. However, differences in the variables related to goal scoring and offense were more significant than in the variables related to defense under the comparisons across competition situations, and the differences in the variables related to defense were mainly detected in the ​yellow card. The number of variables that showed significant differences among match location and match outcome in the group stage were less than in the knockout stage. Therefore, the identified key performance indicators by considering the interactive effects of situational variables may provide detailed and practical insights for coaches to develop useful training interventions and match strategies for upcoming match playing in specific competition situations.